Perancangan Media Edukasi Video Infografis tentang Penerapan Zero Waste pada Skin Care untuk Remaja - Michael Bezaleel; Yohana Enggar; Peni Pratiwi (KK Komunikasi Visual & Multimedia Fakultas Seni Rupa dan Desain Institut Teknologi Bandung, 2023)
Skincare trend that has been happening in Indonesia raises concern regarding plastic waste since most of the skin care packaging is made of plastic and along with the lack of public awareness about the waste problem. Zero Waste principles, especially refuse, reduce, reuse and recycle are applicable to minimize skincare waste. Zero Waste should be educated to young women as they started to take care of themselves using skincare. Motion graphics has the ability to present data and facts regarding skin care waste interestingly and also explain clearly the steps to implement Zero Waste. The research uses a qualitative method with a linear strategy, data collection was carried out by interviewing several sources and the target audience. The result of this research is a motion graphic video that is effective to educate young women about the implementation of Zero Waste in skincare usage. Keywords: Zero Waste, Skincare, Motion Graphic